Polymerase chain reaction as a useful and simple tool for rapid diagnosis of tuberculous meningitis in a brazilian tertiary care hospital - Dora, José Miguel Silva (2012)
Meningitis is a severe and potentially fatal form of tuberculosis. The diagnostic workup involves detection of acid-fast bacilli (AFB) in the cerebrospinal fluid (CSF) by microscopy or culture, however, the difficulty in detecting the organism poses a challenge to diagnosis. The use of the polymerase chain reaction (PCR) in the diagnostic approach to Mycobacterium tuberculosis (MTB) meningitis has been reported as a fast and accurate method, with several commercial kits available. As an alternative, some institutions have been developing inexpensive in house assays. In our institution, we use an in house PCR for tuberculosis. We analyzed the performance of our PCR for the diagnosis of MTB meningitis in 148 consecutive patients, using MTB culture as gold standard. The sensitivity and specificity of CSF PCR for the diagnosis of MTB meningitis was 50% and 98.6% respectively with a concordance with CSF mycobacterial culture of 96% (Kappa=0.52). In contrast to CSF cultures for MTB, our PCR test is a fast, simple and inexpensive tool to diagnose tuberculous meningitis with a performance similar to that obtained with the available commercial kits.